2020
DOI: 10.1007/s12603-020-1327-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Associated Factors Among Oldest-Old in China

Abstract: Objectives: The oldest old population has become the fastest growing segment with excess need of care and social support, it is crucial to improve the health-related quality of life (HRQoL) of these populations. This study seeks to evaluate the health status and to investigate modifiable factors associated with health-related quality of life for oldest old adults in China. Design: A cross-sectional population-based study. Setting: Hainan Province in the south of China. Participants: 1,278 adults aged 80 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…The VAS score records an individual's self-rated health on a 20-cm, vertical visual analog scale ranging from 0 to 100, with notes at both ends labeling "the worst health you can imagine" (at 0) and "the best health you can imagine" (at 100). In our previous study, the mean VAS score was 66.9 among oldest-old populations and the respondents who had good sleeping quality reported higher VAS score by 7.09 on average, compared to those who had poor sleeping quality (48).…”
Section: Visual Analog Scalesmentioning
confidence: 73%
“…The VAS score records an individual's self-rated health on a 20-cm, vertical visual analog scale ranging from 0 to 100, with notes at both ends labeling "the worst health you can imagine" (at 0) and "the best health you can imagine" (at 100). In our previous study, the mean VAS score was 66.9 among oldest-old populations and the respondents who had good sleeping quality reported higher VAS score by 7.09 on average, compared to those who had poor sleeping quality (48).…”
Section: Visual Analog Scalesmentioning
confidence: 73%
“…In this study, several factors related to depression due to chewing problems were identified among various socioeconomic and health-related factors. Especially, HRQoL, one of the risk factors, is related to age-related diseases in the elderly population [ 37 ]. However, chewing problem or depression could be directly affected or complicated by cognitive disorders and chronic diseases; therefore, future studies need to consider age-related diseases as risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…These components were published as healthrelated factors that affect the overall QOL. 33 Park quality had a standardised b=0.17, 95% CI 0.01,0.05, p=0.001. This indicated that the park quality significantly influences the QOL.…”
Section: Discussionmentioning
confidence: 96%